A Corpus-Based Wordlist of Government Official English Examinations - Yotimart, Darunee (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2025)
This study sought to identify the most prevalent content terms in government official examinations for English topics and to analyze the ratio of word families in the General Service List (GSL) and Academic Word List (AWL) inside the Government Official Examination Word List (GOEWL). The English subject government official examinations were aggregated to form the Government Official Examination Corpus. Coxhead’s frequency criterion for the AWL was applied in selecting words for the GOEWL. All word families that appeared once or several times in the examinations were incorporated into the wordlist. AntWordProfiler software was employed to analyze and produce the GOEWL, comprising 3,085 word families. The findings indicated that 83.38 percent of the GOEWL’s word families were part of the first 1,000 of the GSL, 6.22 percent belonged to the second 1,000 of the GSL, 2.41 percent were from the AWL, and the remaining 7.99 percent did not correspond to any wordlists. Students and candidates preparing for government official examinations can build a strong vocabulary through the GOEWL. Educators may adapt the vocabulary list to suit teaching materials, making it more accessible and relevant for students, particularly at the higher education level.